2019
DOI: 10.1515/reveh-2018-0027
|View full text |Cite
|
Sign up to set email alerts
|

Ambient air pollution exposure and lung function assessment of filling station attendants in Ibadan, Nigeria

Abstract: Abstract Background There is an increasing range of adverse health effects associated with air pollution at very low concentrations. Few studies have assessed respiratory parameters among filling station attendants. Objectives This study assessed air pollutants; particulate matter (PM Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The results of examining the relationship between Peak FlowMetry and the prevalence of respiratory complications among gas station workers showed that there is a significant relationship between Peak FlowMetry and the prevalence of respiratory complications. In a study conducted in Nigeria in 2019 by Oni et al [32], FEV1 and PEFR values were found to be very low among gas station attendants, which could possibly be attributed to long-term exposure to air pollutants. Therefore, it can increase the prevalence of respiratory complications among gas station workers.…”
Section: Resultsmentioning
confidence: 95%
“…The results of examining the relationship between Peak FlowMetry and the prevalence of respiratory complications among gas station workers showed that there is a significant relationship between Peak FlowMetry and the prevalence of respiratory complications. In a study conducted in Nigeria in 2019 by Oni et al [32], FEV1 and PEFR values were found to be very low among gas station attendants, which could possibly be attributed to long-term exposure to air pollutants. Therefore, it can increase the prevalence of respiratory complications among gas station workers.…”
Section: Resultsmentioning
confidence: 95%
“…In addition, Olabisi ( 189 ) reported no known occupational health issues among the PSWs, although awareness of safety measures was poor at 10.0%. Oni and Ana ( 190 ) also reported a significantly lower mean peak expiratory flow rate (PEFR) among 100 PSWs in 20 petrol stations.…”
Section: Resultsmentioning
confidence: 97%
“…The PDR-1500 unit is a widely used instrument and shown to be reliable from previous studies. [14][15][16][17][18][19][20][21][22] Over the course of the 2-year period, our low-cost sensors were calibrated four times using the same PDR-1500 unit, where the internal lter was checked to control the real-time measurements gravimetrically. The Airbeam 1 and 2 devices utilize two low-cost sensors: The Shinyei PPD60PV and Plantower PMS 7003 infra-red light scattering particle sensors, respectively.…”
Section: Generation Of Calibration Curves For Cigarette Smokementioning
confidence: 99%